Soluble Expression and Characterization of Biologically Active Bacillus anthracis Protective Antigen in Escherichia coli. (7th February 2016) - Suryanarayana, Nagendra; Vanlalhmuaka,; Mankere, Bharti; Verma, Monika; Thavachelvam, Kulanthaivel; Tuteja, Urmil
Abstract : Bacillus anthracis secretory protein protective antigen (PA) is primary candidate for subunit vaccine against anthrax. Attempts to obtain large quantity of PA from Escherichia coli expression system often result in the formation of insoluble inclusion bodies. Therefore, it is always better to produce recombinant proteins in a soluble form. In the present study, we have obtained biologically active recombinant PA in small scale E. coli shake culture system using three different expression constructs. The PA gene was cloned in expression vectors bearing trc, T5, and T7 promoters and transformed into their respective E. coli hosts. The growth conditions were optimized to obtain maximum expression of PA in soluble form. The expression construct PA-pET32c in DE3-pLysS E. coli host resulted in a maximum production of soluble PA (15 mg L −1 ) compared to other combinations. Purified PA was subjected to trypsin digestion and binding assay with lethal factor to confirm the protein's functionality. Biological activity was confirmed by cytotoxicity assay on J774.1 cells. Balb/c mice were immunized with PA and the immunogenicity was tested by ELISA and toxin neutralization assay. This study highlights the expression of soluble and biologically active recombinant PA in larger quantity using simpler E. coli production platform.